Evaluation of serum levels of MDA and Vitamins A, E, and C in Recurrent Aphthous Stomatitis - Heidar khademi; Farnaz Tavangar; Sima Amini; Atefeh Tavangar (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Minor aphthous stomatitis, with an unknown etiology, is a recurrent inflammatory oral condition, which affects almost 20% of the population. Hereditary, hematologic and immunologic factors have been reported to be the main etiologic factors for aphthous stomatitis. Another factor has been reported to be an imbalance between oxidative and anti-oxidative agents in the body. The aim of this study was to evaluate the amount of lipid peroxidase and anti-oxidative vitamins in the sera of patients with recurrent aphthous stomatitis (RAS). Materials and methods: In this cross-sectional descriptive-analytical study, 25 patients suffering from RAS were compared with 24 healthy individuals. ELISA was used to determine serum lipid peroxidase of which malondialdehyde (MDA) is an indicator, as well as vitamins A, E and C levels in a fasting state in both groups. The results were analyzed by SPSS 11.5 using t-test and chi-squared test (α=0.05).Results: No significant differences were detected in serum levels of vitamins A, E and C and MDA between the patient and control groups (p values = 0.53, 0.53, 0.78, and 0.32, respectively). Conclusion: Under the limitations of the present study there was no relationship between RAS ulcers and serum levels of vitamins A, E and C and MDA. Further studies are necessary in this regard.Key words: Aphthous, Malondialdehyde, Serum, Stomatitis, Vitamin.